N-Terminal Pro B-Type Natriuretic Peptide's Usefulness for Paroxysmal Atrial Fibrillation Detection Among Populations Carrying Cardiovascular Risk Factors - Palà, Elena; Bustamante, Alejandro; Clúa-Espuny, Josep Lluis; Acosta, Juan; Gonzalez-Loyola, Felipe; Ballesta-Ors, Juan; Gill, Natalia; Caballero, Andrea; Pagola, Jorge; Pedrote, Alonso; Muñoz, Miguel Angel; Montaner, Joan (Frontiers in Neurology, 2019)
Background: Atrial fibrillation (AF) systematic screening studies have not shown a clear usefulness in stroke prevention, as AF might be presented as paroxysmal and asymptomatic. This study aims to determine the usefulness of some blood-biomarkers to identify paroxysmal atrial fibrillation in the context of a screening program. Methods: 100 subjects between 65-75 years with hypertension and diabetes were randomly selected. AF was assessed by conventional electrocardiogram (ECG) and four weeks monitoring with a wearable Holter device (NuuboTM). N-terminal pro B-type natriuretic peptide (NT-proBNP), Apolipoprotein CIII (ApoC-III), von Willebrand factor (vWF), ADAMTS13, urokinase plasminogen activator surface receptor (uPAR) and urokinase plasminogen activator (uPA) were determined in serum/plasma samples and the levels were compared depending on AF presence and mode of detection. Results: AF prevalence in the studied population was found to be 20%. In 7 subjects AF was only detected after one-month monitoring (h-AF group). NT-proBNP levels were higher in subjects with AF compared with subjects with no AF (p<0.0001), even when only taking into account h-AF group (p=0.031). No significant differences were found in the other biomarkers. NT-proBNP >95pg/ml cut-off showed high sensitivity and specificity to detect AF (95%, 66.2%) or h-AF (85.72%, 66.2%) and was found to be an independent predictor of AF and h-AF in a logistic regression analysis. NT-proBNP correlates with AF burden (r=0.597, p=0.024). Conclusion: NT-proBNP was elevated in AF cases not identified with ECG, thus, it may be used as screening biomarker in asymptomatic high risk populations with a promising cut-off point of 95 pg/ml that requires further validation.